Sebuah Jalur Hidup Digital: Penerimaan Pengguna Terhadap Aplikasi Deteksi Penyakit Jantung Koroner - Wikarsa, Liza; Sanger, Junaidy; Taulu, Angelica (Jurnal Pekommas, 2024)
Cardiovascular disease, especially coronary heart disease (CHD), is the leading cause of death globally, with Indonesia, particularly North Sulawesi, experiencing significant prevalence due to unhealthy lifestyles. This study aims to assess the adoption and utilization of an early detection application for CHD among residents of the Spiritual Region of the Sacred Heart of Mary Cathedral Parish in Manado. It also seeks to identify opportunities for enhancing user experiences with the application using the Technology Acceptance Model (TAM). TAM includes constructs like perceived usefulness (PU), perceived ease of use (PEU), attitude towards use (ATU), behavioral intention to use (BIU), actual system use (ASU), and three external variables: information quality (PUIQ), service quality (PEUSVQ), and system quality (PEUSQ). This study uses the Partial Least Square (PLS) approach for data analysis. The results confirmed that all measures effectively assess their intended constructs. Strong correlations among the constructs demonstrate solid internal consistency. Regarding reliability, all constructs demonstrate acceptable consistency